Cryptosporidiosis in children less than three years old in Ciliwung Riverside, Kampung Melayu Village, Jakarta, Indonesia - Herbowo A. Soetomenggolo; Agus Firmansyah; Agnes Kurniawan; Partini P. Trihono (Indonesian Pediatric Society Publishing House, 2008)
Background Cryptosporidium infection is often found in children, especially children below three years old. Many risk factors can affect cryptosporidiosis prevalence. At this moment, the prevalence and risk factors of cryptosporidiosis in children in Jakarta are unknown. Objectives To determine the cryptosporidiosis prevalence, clinical manifestations, and risk factors in children below three years old. Methods This cross sectional study involved 474 subjects between the age of 0 to 35 months in Ciliwung riverside, Kampung Melayu village, from December 2005 until April 2006. Stool specimens were examined using modified acid-fast staining. Nutritional status was measured based on actual body weight over ideal body weight ratio (NCHS-CDC 2000). Results Cryptosporidium cysts were found in stool sample of 10/ 474 subject (2.1%). Most of the cases used ground water as a source for drinking and washing. All positive cases lived in houses with bad sanitation, flooded house and 9/10 cases had a crowded household. Cat and mice were the two most frequently found animals around the house. We found five asymptomatic cases and all of the cases were undernourished. Conclusions The prevalence of cryptosporidiosis in this study is 2.1%. Due to small number of cases no risk factor could be identified. Use of groundwater as a water source, bad sanitation, cat and mice around the house, flooded house, crowded household and undernourishment might be related to cryptosporidiosis prevalence. Half of the infected children were asymptomatic.